Isotopic constraints on the formation pathways and sources of atmospheric nitrate in the Mt. Everest region. (December 2020) - Wang, Kun; Hattori, Shohei; Kang, Shichang; Lin, Mang; Yoshida, Naohiro
Abstract: Inorganic particulate nitrate (p- NO 3 − ), gaseous nitric acid (HNO3(g) ) and nitrogen oxides (NOx  = NO + NO2 ), as main atmospheric pollutants, have detrimental effects on human health and aquatic/terrestrial ecosystems. Referred to as the 'Third Pole' and the 'Water Tower of Asia', the Tibetan Plateau (TP) has attracted wide attention on its environmental changes. Here, we evaluated the oxidation processes of atmospheric nitrate as well as traced its potential sources by analyzing the isotopic compositions of nitrate (δ 15 N, δ 18 O, and Δ 17 O) in the aerosols collected from the Mt. Everest region during April to September 2018. Over the entire sampling campaigns, the average of δ 15 N( NO 3 − ), δ 18 O( NO 3 − ), and Δ 17 O( NO 3 − ) was −5.1 ± 2.3‰, 66.7 ± 10.2‰, and 24.1 ± 3.9‰, respectively. The seasonal variation in Δ 17 O( NO 3 − ) indicates the relative importance of O3 and HO2 /RO2 /OH in NOx oxidation processes among different seasons. A significant correlation between NO 3 − and Ca 2+ and frequent dust storms in the Mt. Everest region indicate that initially, the atmospheric nitrate in this region might have undergone a process of settling; subsequently, it got re-suspended in the dust. Compared with the Δ 17 O( NO 3 − ) values in the northern TP, our observed significantly higher values suggest that spatial variations in atmospheric Δ 17 O( NO 3 − ) exist within the TP, and this might result from the spatial variations of the atmospheric O3 levels, especially the stratospheric O3, over the TP. The observed δ 15 N( NO 3 − ) values predicted remarkably low δ 15 N values in the NOx of the sources and the N isotopic fractionation plays a crucial role in the seasonal changes of δ 15 N( NO 3 − ). Combined with the results from the backward trajectory analysis of air mass, we suggest that the vehicle exhausts and agricultural activities in South Asia play a dominant role in determining the nitrate levels in the Mt. Everest region. Graphical abstract: Image 1 Highlights: Isotopic compositions of atmospheric nitrate in Mt. Everest region were reported. Importance of O3 and HO2 /RO2 /OH in NOx oxidation processes changed among seasons. Spatial variations in atmospheric Δ 17 O(NO3 – ) exist within TP. N isotopic fractionation plays a crucial role in seasonal changes of δ 15 N(NO3 – ). Vehicle exhaust and agricultural activities in South Asia are main NOx sources. Abstract : Main findings: Importance of O3 and HO2 /RO2 /OH in NOx oxidation processes changed among different seasons; vehicle exhausts and agricultural activities in South Asia are the main NOx sources.